2021
DOI: 10.7759/cureus.13048
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Umbilical Cord Hematoma

Abstract: Spontaneous umbilical cord hematoma is a rare complication with a usually benign course but is potentially fatal without vigilant and timely medical intervention. We present the case of a 23-year-old primigravida mother who presented in labor. She was placed on continuous fetal heart rate monitoring, which showed two episodes of fetal heart rate tracing of the category II variety. The labor was induced with oxytocin, and the ammonitic membrane was incised artificially. The baby was male, term at 38 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In 2009, Towers et al 32 and Barbati et al 33 also reported similar cases, which were discovered spontaneously by a fetal heart monitor in the USA and Italy. Recently, Koukoura et al 12 and Khatiwada et al 15 also reported on two cases that were similar to this event, with the precious experience on continuous FHRm in surveillance of labour.…”
Section: Discussionmentioning
confidence: 58%
“…In 2009, Towers et al 32 and Barbati et al 33 also reported similar cases, which were discovered spontaneously by a fetal heart monitor in the USA and Italy. Recently, Koukoura et al 12 and Khatiwada et al 15 also reported on two cases that were similar to this event, with the precious experience on continuous FHRm in surveillance of labour.…”
Section: Discussionmentioning
confidence: 58%
“…In 2009, Tower CV et al and A. Barbati et al also report the similar case discovered spontaneously by fetal heart monitor in USA and in Italy ( 29 ), ( 30 ). Recently, Koukoura et al and Khatiwada P et al also reported 3 cases related to this event with the precious experience on continuous FHRm in surveillance of labor ( 11 ), ( 15 ).…”
Section: Discussionmentioning
confidence: 97%
“…Haematomas of the cord produced by the extravasation of blood from the umbilical vein to Wharton's jelly have also been described. Although they are infrequent, they can be spontaneous [39] and have a benign course. However, they are usually associated with invasive procedures, infections or morphological abnormalities [40].…”
Section: Other Vascular Disordersmentioning
confidence: 99%